Philometrid nematodes (Philometridae) of marine teleosts from Balinese waters, Indonesia, including the description of Philometra damriyasai sp. nov. - Dewi, Kartika; Palm, Harry W. (Zootaxa, 2017)
Based on light and scanning electron microscopy, one new species of philometrid nematodes, Philometra damriyasai sp. nov. (Nematoda: Dracunculoidea: Philometridae) from the body cavity of Tylerius spinosissimus (Regan, 1908) (Tetraodontiformes, Tetraodontidae), and five known species are reported in different marine teleosts from South Bali, Indonesia. The new species can be distinguished from the most closely related P. javensis Moravec, Walter & Juniar, 2012 by the absence of sclerotized denticles on the cuticle of the anterior oesophageal lobes of the mouth and smaller larvae. Philometra nemipteri Luo, 2001 of Nemipterus japonicus (Bloch, 1791), P. otolithi Moravec & Manoharan, 2013 of Otolithes ruber (Bloch & Schneider, 1801) (both from gonads) and Philometroides marinus Moravec & Buron, 2009 from the body cavity of Rachycentron canadum (Linnaeus, 1766) are reported for the first time from Indonesian waters, thus extending their range of distribution into the tropical Indo-Pacific Ocean. Philometra lobotidis Moravec, Walter & Yuniar, 2012 from the body cavity of Lobotes surinamensis (Bloch, 1790) and P. ocularis Moravec, Ogawa, Suzuki, Miyaki & Donai, 2002 from the eye cavity of Variola louti (Forsskål, 1775) represent new geographical records, and Philometra sp. was recorded for the first time from Cephalopholis sexmaculata (Rüppell, 1830). A total of 14 philometrids have been so far identified from marine fishes in Indonesia.